Effect of double stratification on boundary layer flow and heat of nanofluid over a vertical plate in the presence of chemical reaction - Rahamat, Lily Afizah (2015)
The problem of double stratification on boundary layer flow and heat transfer induced due to a nanofluid over a vertical plate in the presence of chemical reaction is investigated. Nanoparticles have a great potential to improve the thermal transport properties compared to conventional particles fluids suspensions, mili meter and micro meter sized particles. The transport equation which employed in the analysis including the effect of Brownian motion, thermophoresis parameter, buoyancy ratio parameter, thermal stratification parameter, solutal stratification parameter and chemical reaction rate parameter. The non-linear governing equations and their associated boundary conditions are initially cast into dimensionless forms by similarity variables. The resulting systems of equations are then solved numerically by using very robust computer algebra software MAPLE 18. This software uses a fourth-fifth order Runge Kutta Fehlberg method as a default to solve boundary values problems numerically using the dsolve command. Numerical results are obtained for dimensionless velocity, temperature and concentration distribution of particles. It is examined that the dimensionless velocity of the fluid decreases with the increases of thermal and solutal stratification parameter. The numerical results are compared and found to be in good agreement with the previous published result on special cases of the problem.